Treatment of refractory immune-mediated necrotizing myopathy with efgartigimod - Yang, MengTing; Yuan, JingChu; Wang, YiKang; Hao, HongJun; Zhang, Wei; Wang, ZhaoXia; Yuan, Yun; Zhao, YaWen (Frontiers in Immunology, 2024)
Objective: We aimed to explore the efficacy and safety of efgartigimod in patients with refractory immune-mediated necrotizing myopathy (IMNM).Methods: This open-label pilot observational study included seven patients with refractory IMNM, all of whom received intravenous efgartigimod treatment. The clinical response was assessed after 4 weeks of efgartigimod treatment according to the 2016 American College of Rheumatology-European League Against Rheumatism response criteria for adult idiopathic inflammatory myopathy. Serum levels of immunoglobulin, and anti-signal recognition particle (SRP) and 3hydroxy-3-methylglutaryl-CoA reductase (HMGCR) antibodies, were measured using enzyme-linked immunosorbent assays and commercial line immunoblot assays. Safety assessments included evaluations of adverse events and severe adverse events.The seven patients with refractory IMNM included five cases with anti-HMGCR antibodies and two cases within anti-SRP antibodies. Four out of seven patients achieved clinical responses. The TIS for the responders at 4 weeks were 32.5, 40.0, 47.5, and 70.0, and those at 8 weeks were 27.5, 47.5, 57.5, and 70.0. In comparison to the responsive patients, the non-responsive patients had longer durations (8[-] versus 2 [1-5] years, P=0.03), and more chronic myopathic features by muscle biopsy (67% versus 0%, P=0.046). Serum immunoglobulin G levels (11.2 ± 2.5 versus 5.7 ± 2.5, P=0.007) and anti-HMGCR/SRP antibody levels (97.2 ± 6.9 versus 41.8 ± 16.8, P=0.002) were decreased after treatment compared with baseline levels. Adverse events were reported in one of the seven patients, who showed mild headache.Conclusions: Despite its small size, our study demonstrated that promoting the degradation of endogenous immunoglobulin G may be effective for patients with IMNM. Efgartigimod may be a promising option for cases of refractory IMNM, to shorten duration and minimize chronic myopathic features.